2014
DOI: 10.15850/amj.v1n1.289
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Topical Application of Binahong [Anredera cordifolia (Ten.) Steenis] Leaf Paste in Wound Healing Process in Mice

Abstract: Background: Wound caused by trauma poses challenging daily clinical problems for physicians in hospitals and other health services. It has high risk for mortality and morbidity. Binahong [Anredera Cordifolia (Ten.) Steenis] plant originates from China and can be found abundantly in Indonesia. The objective of this research is to investigate the effect of topical application of Binahong leaf paste on wound healing process.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 9 publications
0
7
0
Order By: Relevance
“…Based on research by Miladiyah and Prabowo in 2012, it was stated that the ethanol extract of binahong leaves in concentrations of 20% and 40% was effective in healing 2 cm incision wounds in guinea pigs (Miladiyah & Prabowo, 2012). The same thing was done by Singh, et al in 2014 showed that topical administration of binahong leaf paste showed better results in healing 1 cm² incisional wounds in mice (Musmuscularis) (Gurcharan Singh et al, 2014). The results of research conducted by Violante, et al 2020 stated that the flavonoids in the hydroethanol extract of dried Fridericia chica leaves showed good antibacterial activity against Gram-negative and Gram-positive bacteria including Streptococcus pyogenes, Pseudomonas aeruginosa, Staphylococcus epidermidis, Staphylococcus aureus, and Salmonella typhimurium (Violante et al, 2021).…”
Section: Introductionmentioning
confidence: 89%
“…Based on research by Miladiyah and Prabowo in 2012, it was stated that the ethanol extract of binahong leaves in concentrations of 20% and 40% was effective in healing 2 cm incision wounds in guinea pigs (Miladiyah & Prabowo, 2012). The same thing was done by Singh, et al in 2014 showed that topical administration of binahong leaf paste showed better results in healing 1 cm² incisional wounds in mice (Musmuscularis) (Gurcharan Singh et al, 2014). The results of research conducted by Violante, et al 2020 stated that the flavonoids in the hydroethanol extract of dried Fridericia chica leaves showed good antibacterial activity against Gram-negative and Gram-positive bacteria including Streptococcus pyogenes, Pseudomonas aeruginosa, Staphylococcus epidermidis, Staphylococcus aureus, and Salmonella typhimurium (Violante et al, 2021).…”
Section: Introductionmentioning
confidence: 89%
“…Picture histopathology shows that the on-base group is visible cell fibroblast accompanied with fiber less collagen solid, different with group nanogels extract binahong leaf 3% showing many cells formed fibroblasts with accompanied fiber dense collagen. This can be caused by the phytochemicals content on the binahong leaf, flavonoids and saponins increase the proliferation of fibroblasts and stimulate the collagen formation on the proliferation phase, which can speed up wound healing [21,22].…”
Section: Osteoblastmentioning
confidence: 99%
“…In addition to having an antimicrobial effect, the active compound content of binahong leaves can also play a role in the tissue healing process because when used in certain doses it is not toxic and has a role as an antioxidant, anti-inflammatory, and antibacterial so that it can be used in the wound healing process [30]. Saponin compounds can increase monocyte proliferation thereby helping to increase the number of macrophages that will secrete growth factor TGF-β1 which will play a role in various phases of wound healing [31,32]. The content of tannins and triterpenoids which act as antibacterial also acts as an astringent in wounds and helps in the differentiation process of myofibroblasts [33,34].…”
Section: Calculation Of Ic 50 Valuementioning
confidence: 99%